Analysis of socio-economic factors of fish pond production in Enugu State, Nigeria - Adeosun, K. P.; Ume, C. O.; Ezugwu, R. U. (Journal of Tropical Agriculture, 2019)
The study determined the socioeconomic factors of fish pond production by assessing cost and returns, and the effect of socioeconomic factors on net-income from fish ponds, as well as its constraints. Primary data were used for the study. A systematic random sampling technique was employed to select 120 fish farmers from the list provided by the Fish Farmers Association in the State. Data collected were analyzed using descriptive statistics, budgeting analysis, Ordinary Least Square (OLS) and Quantile regression. The study revealed that the mean age, household size, years spent in school and fish farming experience were 41 years, 5 people, 15 years and 3.6 years, respectively. The result showed that the average net farm income of fish farmers in the State was 41,902 and gross margin was 46,635. The profitability indices such as benefit-cost ratio (1.4), return on investment (1.45), return on variable cost (2.58), net farm income margin (0.58) and gross ratio (30.64) were positive. The result of multiple regression showed that fish pond production experience and number of ponds per farmer were significant at OLS and all the quantile levels. Size of ponds was significant at OLS and 75th quantile. Likewise, access to credit and male household size were significant at OLS, and 55th and 75th quantile. Results indicate that government and private sectors should invest in fish pond production to subsidize costly inputs in fish production and important socioeconomic factors should be institutionalized.